Study of Theory Based on Security at Silimo Settlement in The Baliem Valley of Papua - Salipu, Muhammad Amir; Nurmaningtyas, Anggia Riani; Zebua, Mercyana Trianne; Santoso, Imam (University of Merdeka Malang, 2022)
In the Baliem Valley, Papua, the tradition of tribal wars in the culture of the Hubula tribe in the past is related to the concept of site selection, spatial planning, and building form in the Silimo settlement. The problem in this study is how the selection of location, spatial planning, building form, and territoriality become the concept of security in a traditional settlement. The purpose of the study was to determine the security concept in traditional Silimo settlement that consists of site selection, spatial planning, building form, and territoriality based on security theory in settlements. In answering the problem of this research, the researchers use qualitative research methods. The researchers also use a phenomenological approach to explain or reveal the meaning of concepts or phenomena of experience based on the awareness that occurs in several individuals related to security in the Silimo settlement. The theories used in this research are the security theory in crime prevention and the theory of defensible space. The result of this research is that security theory can explain that the selection of location, spatial planning, and building form in the Silimo settlement of the Hubula Tribe in the Baliem Jayawijaya Valley was built based on the traditional conception of security. The concept of security in the Silimo settlement can be realized by: 1) The concept of territory as a defense space and territory as a territory of power; 2) The concept of space as a personal space and a public space: 3) The concept of Kinship, confederation, norms, customary rituals, which become the Patterns and Concepts of Space and Building Forms and Constructions are forms of Social Relations, Natural Relations and Ancestral Relations, to actualize a security system in Silimo settlement.